Analisis Framing Pemberitaan Kontroversial Campaign Zara “The Jacket” Singgung Korban Gaza Pada BBC News & Suara.com - Afni Tiana Rosa; Andri Prasetyo Yuwono (Universitas Tarakanita, 2024)
This research focuses on how online media presented the news of the controversial case of the ZARA Atelier